Factors associated with mouthguard use and discontinuation among rugby players in Malaysia - Liew, A.K.C.; Abdullah, D.; Noorina, W.A.W.; Khoo, S. (Blackwell Publishing, 2014)
Aims To assess rugby players' preferences for using a mouthguard and to determine the factors contributing to the use and discontinuation of a mouthguard.